2010
DOI: 10.1128/aac.00128-10
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of a Plasmid-Borne bla OXA-58 Gene with Its Hybrid Promoter Provided by IS 1006 and an IS Aba3 -Like Element to β-Lactam Resistance in Acinetobacter Genomic Species 13TU

Abstract: The contribution of the bla OXA-58 gene and its promoter to ␤-lactam resistance has not been validated in Acinetobacter spp. other than Acinetobacter baumannii. We identified a multidrug-resistant (including carbapenem resistance) Acinetobacter genomic species 13TU in which bla OXA-58 was the only detected carbapenemase gene. The bla OXA-58 gene was plasmid located, flanked by ISAba3 (downstream) and an ISAba3-like element (upstream). An IS1006 element was inserted into ISAba3-like (IS1006-⌬ISAba3-like) to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…These strains harbored neither bla OXA-23 nor bla OXA-58 . On the other hand, in the isolate 2199, we observed the presence of imipenem-resistant subpopulations in accordance with a previous report by Chen et al (2010) who demonstrated that ISAba3-like bla OXA-58 could mediate resistance to penicillin derivatives but only heteroresistance to carbapenems.…”
supporting
confidence: 93%
“…These strains harbored neither bla OXA-23 nor bla OXA-58 . On the other hand, in the isolate 2199, we observed the presence of imipenem-resistant subpopulations in accordance with a previous report by Chen et al (2010) who demonstrated that ISAba3-like bla OXA-58 could mediate resistance to penicillin derivatives but only heteroresistance to carbapenems.…”
supporting
confidence: 93%
“…S1 in the supplemental material). The generation of electrocompetent cells and electrotransformation were performed as previously described (20). Restriction enzymes were purchased from New England BioLabs (Beverly, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria belonging to the family Enterobacteriaceae and Pseudomonas aeruginosa were identified using a Vitek II system (bioMéri-eux, Marcy l'Etoile, France). Genes encoding class A, B, and D carbapenemases and the upstream insertion sequence of CHDL genes were detected by a PCR method, as previously described (19,20). Phenotypic tests were used to identify class B metallo-␤-lactamases, as previously described (20).…”
Section: Methodsmentioning
confidence: 99%